Two-dimensional peptide nanosheets functionalized with gold nanorods for photothermal therapy of tumors. Issue 15 (3rd April 2023) - Kong, Hao; Han, Jinru; Yang, Ming; Lai, Liangxue; Sun, Yabing; Luan, Xin; Ren, Wenzhi; Wu, Aiguo; Wei, Gang
Abstract : Self-assembled peptide nanosheets functionalized with gold nanorods provide a functional nanoplatform for photothermal therapy of tumors. Abstract : Self-assembled peptide nanomaterials exhibit great potential for applications in materials science, energy storage, nanodevices, analytical science, biomedicine, tissue engineering, and others due to their tailorable ordered nanostructures and unique physical, chemical, and biological properties. Although one-dimensional peptide nanofibers and nanotubes have been widely used for biomedical applications, the design and synthesis of two-dimensional (2D) peptide nanostructures for cancer therapy remain challenging. In this work, we describe the creation of 2D biocompatible peptide nanosheets (PNSs) through molecular self-assembly, which can provide support matrixes for conjugating gold nanorods (AuNRs) to form high-performance 2D nanomaterials for photothermal conversion. After molecular modification, AuNRs can be chemically conjugated onto the surface of 2D PNSs, and the created PNS-AuNR nanohybrids serve as a potential nanoplatform for photothermal therapy of tumor cells. The obtained results indicate that both PNSs and AuNRs contribute to the improved efficiency of photothermal therapy (PTT) of tumors, in which 2D PNSs provide high biocompatibility and a large surface area for binding AuNRs, and AuNRs show a high PTT ability towards tumors. The strategies of molecular design and functional tailoring of self-assembled peptide nanomaterials shown in this study are valuable and inspire the synthesis of biomimetic nanomaterials for biomedicine and tissue engineering applications.